PENGENALAN MATEMATIKA REALISTIK KEPADA MASYARAKAT BELAJAR DI KELURAHAN IRINGMULYO - Endah Wulantina; Zahwa Eza Soeseno; Farida Arsita; Selvi Loviana; Annisa Ayu Ulil Amri; Pika Merliza (Bakti Cendana, 2020)
The aim of this dedication is that it is expected that the community learning grade 4 elementary schools around the area will no longer find it difficult to understand mathematics after the introduction of learning that links mathematics with everyday life (Realistic Mathematics). This dedication uses a qualitative approach with descriptive methods. The props used in this service are traditional snacks in the form of triangles and tempeh. Dedication was carried out for 4 meetings with 20 students. The results of the evaluation of the implementation of community service: 1) The community learns at the elementary school level (SD) get new knowledge and learning experiences in mathematics by using Realistic Mathematics (MR). 2) Learning using Realistic Mathematics (MR) increases students' interest and curiosity about mathematics. 3) By using Realistic Mathematics (MR) learning, students' understanding of mathematics becomes easier, so mathematics is no longer considered difficult. 4) The learning process becomes more colorful and meaningful with the use of Realistic Mathematics (MR) learning. 5) People learn to feel mathematics is a pleasant lesson seen from their enthusiasm when the learning process is ongoing.